Evaluation of Different Mode of Action Insecticides for the Control of Bemisia tabaci; Enhancement of Pesticide Efficacy - Jackie Dunn; Debbie Ann Collins; Neil Audsley (Insects)
Bemisia tabaci (Gennadius) is a major pest worldwide, causing damage to a vast range of plants through its feeding on phloem sap and its vectoring of >100 plant viruses. Although not established in the UK, it is regularly introduced on planting material, which poses a significant plant health risk. Restrictions on pesticide use and increasing resistance to available active ingredients limit options for effective control of potential outbreaks. Alternative management options are required to mitigate this risk. There was high variability in the efficacy of the different modes of action products tested against two life stages (adults and larvae) as well as the Middle East–Asia Minor 1 (MEAM1) and Mediterranean (MED) cryptic species of B. tabaci. For both adults and larvae, MEAM1 were more susceptible than MED insects, possibly due to differences in resistance developed against some active ingredients. All products tested were effective to varying degrees against MEAM1 adults with Tracer (spinosad), PREV-AM (orange oil), Sequoia (sulfoxaflor), and FLiPPER (fatty acids) having similar efficacies (59–78% mortality). In contrast, PREV-AM and FLiPPER were most effective against MED adults (74% and 65% mortalities, respectively). Both MED and MEAM1 larvae were highly susceptible to FLiPPER and PREV-AM (>95% mortality), and the efficacy of Tracer and FLiPPER can be enhanced by using in combination with PREV-AM, and this can be achieved by using low doses of each product. Synergy was measured between PREV-AM and Tracer against MEAM1 larvae, which has the potential to provide effective control with a reduced pesticide application.